Platfrom Video Game sebagai Media Terapeutik - Yunike Yunike; Ira Kusumawaty (Journal of Telenursing (JOTING), 2023)
This study attempts to use video games therapeutically, which can be used as a rationale for developing and utilizing video games as a therapeutic medium. This research method uses the PRISMA approach using the keywords "video game" and "teenagers," "mental health," and "intervention" in the Scopus electronic database, google scholar, Science Direct and Pubmed with a range of years 2018 to 2022. Based on the research results, they have identified the definition of video games along with their platforms and the use of video games to improve mental health for humans of all ages, especially adolescents. It is proven that improving the physical condition of older adults can involve the role of video games as a medium in them. In conclusion, thus, the study of the development and use of video games is urgent to help improve human health status. Keywords: Adolescent Mental Health, Therapeutic Media, Video Games